Address Filtering Based Wu-Manber Multiple Patterns Matching Algorithm - Baojun Zhang; Xiaoping Chen; Lingdi Ping; Zhaohui Wu (2009 Second International Workshop on Computer Science and Engineering, 2009)
Wu-Manber is a widely used multiple patterns matching algorithm. But in practical application, it exist the following limitations. First, there are redundant information and operations. Second, the prefix table is established, but is hardly used. Third, need to traverse the whole link list. These limitations make the algorithm complicated and affect the performance of it. Though some limitations have been indicated by others, different ways are taken in this paper. Prefix table is used to filter the patterns. Address filtering based search method avoids traversing the whole link list. Experimental result shows that the improved algorithm has a good performance than the original one.